Fist of the North Star. Volume 2 - Buronson, 1947- (Viz signature., 2021)
"In a postapocalyptic world, humanity has risen from the ashes of nuclear war to a nightmare of endless suffering. It is a time of chaos. Warlords and gangs of savage marauders rule the broken ruins of civilization, terrorizing and enslaving the survivors. Life has become a brutal struggle for existence and death the only release. One day, a wanderer appears out of the wasteland to bring justice to the guilty and hope to the people--a warrior named Ken, a man who bears seven scars upon his chest and holdsthe secret of a mysterious martial art known as Hokuto Shinken, the Divine Fist of the North Star!"--